NMR metabolomics to study the metabolic response of human osteoblasts to non‐poled and poled poly (L‐lactic) acid. (24th June 2019) - Araújo, Rita; Carneiro, Tatiana J.; Marinho, Paula; da Costa, Marisa Maltez; Roque, Ana; da Cruz e Silva, Odete A. B.; Fernandes, Maria Helena; Vilarinho, Paula M.; Gil, Ana M.
Abstract: Untargeted nuclear magnetic resonance (NMR) metabolomics was employed, for the first time to our knowledge, to characterize the metabolome of human osteoblast (HOb) cells and extracts in the presence of non‐poled or negatively poled poly‐L‐lactic acid (PLLA). The metabolic response of these cells to this polymer, extensively used in bone regeneration strategies, may potentially translate into useful markers indicative of in vivo biomaterial performance. We present preliminary results of multivariate and univariate analysis of NMR spectra, which have shown the complementarity of lysed cells and extracts in terms of information on cell metabolome, and unveil that, irrespective of poling state, PLLA‐grown cells seem to experience enhanced oxidative stress and activated energy metabolism, at the cost of storage lipids and glucose. Possible changes in protein and nucleic acid metabolisms were also suggested, as well as enhanced membrane biosynthesis. Therefore, the presence of PLLA seems to trigger cell catabolism and anti‐oxidative protective mechanisms in HOb cells, while directing them towards cellular growth. This was not sufficient, however, to lead to a visible cell proliferation enhancement in the presence of PLLA, although a qualitative tendency for negatively poled PLLA to be more effective in sustaining cell growth than non‐poled PLLA was suggested. These preliminary results indicate the potential of NMR metabolomics in enlightening cell metabolism in response to biomaterials and their properties, justifying further studies of the fine effects of poled PLLA on these and other cells of significance in tissue regeneration strategies. Abstract : PLLA is a biomaterial used in bone regeneration, with limited knowledge as to the metabolic adaptation of bone cells, to determine either positive or negative responses to implantation procedures. This paper unveils novel metabolic information of osteoblastic response to PLLA in different polarization states. Cell response seems to involve glucose and lipids catabolism, anti‐oxidative stress mechanisms and proteins and membrane phospholipids biosynthesis, apparently independently of polymer poling state. Metabolic profiling is promising in the monitoring biomaterial's performance in tissue regeneration.